The impact of foot and mouth disease - Rushton, Jonathan; Knight-Jones, Theodore J.D. (Food and Agriculture Organization of the United Nations and the World Organisation for Animal Health, 2015)
The global impact of foot and mouth disease (FMD) is colossal because of the huge numbers of animals affected. This impact can be separated into two components: direct losses due to a reduction in production and changes in herd structure; and indirect losses that relate to the significant costs of FMD control and management and poor access to markets and limited use of improved production technologies. The paper estimates that the annual impact of FMD in terms of production losses and vaccination alone are in the region of US$ 5 billion.